The Baby Café concept as an international network of support to breastfeeding - Isabel Baño Piñero; César Carrillo García; Uma Thambidurai; María Emilia Martínez Roche (Universidad de Alicante, 2015)
The general objective of this work is to reflect on the phenomenon of The Baby Café as a novel and convenient concept in a world of promotion, protection and support of breastfeeding worldwide. The Baby Café is an initiative to support breastfeeding that coordinates an international network of centers that combines formal support from health professionals who specialize in lactation with informal support groups or networks of breastfeeding. With the ultimate goal of the promotion, protection and support of breastfeeding, the introduction of The Baby Café initiative encourages more studies of such nature to be conducted, eventually demonstrating the true impact of such initiatives on society; we have developed, through the theoretical framework and a field diary, a qualitative study, which has allowed us to explore the phenomenon of the Baby Cafe in the 10th district of Singapore, during the month of March 2015.